2000
DOI: 10.1046/j.1464-5491.2000.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of autoantibodies to glutamic acid decarboxylase across the spectrum of diabetes mellitus seen in South Africa

Abstract: Auto-immune beta-cell destruction has an important role in the pathogenesis of Type 1 DM amongst African patients. However, Type 2 African DM patients and other diabetes subtypes are largely GAD-AB-negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 21 publications
2
30
1
2
Order By: Relevance
“…In Caucasian population, the prevalence of islet cell-associated antibodies in recently diagnosed subjects with T1DM ranged from 80% to 97% (Diabetes Prevention Trial -Type 1 Diabetes Study Group, 2002;Landin-Olsson et al, 1992;Notkins & Lernmark, 2001). The prevalence in our study was comparable to that of Asians (Lee, Ng, Thai, Lui, & Loke, 2001;Todd, Ng, Lui, & Thai, 2004;Zimmet et al, 1993) where it was reported at 5-40% and Africans (Hawa et al, 2005;Lutale et al, 2007;Oli et al, 1981;Panz et al, 2000) which ranged 7-44%, including what was reported in Ethiopia in the 1980s and in 2011 (Gill et al, 2011;Peters et al, 1986). We think that part of the reason why the antibody positivity in our T1DM patients was relatively lower is the fact that most of our T1DM patients were not newly diagnosed as indicated by the mean duration of diabetes.…”
Section: Discussionsupporting
confidence: 51%
“…In Caucasian population, the prevalence of islet cell-associated antibodies in recently diagnosed subjects with T1DM ranged from 80% to 97% (Diabetes Prevention Trial -Type 1 Diabetes Study Group, 2002;Landin-Olsson et al, 1992;Notkins & Lernmark, 2001). The prevalence in our study was comparable to that of Asians (Lee, Ng, Thai, Lui, & Loke, 2001;Todd, Ng, Lui, & Thai, 2004;Zimmet et al, 1993) where it was reported at 5-40% and Africans (Hawa et al, 2005;Lutale et al, 2007;Oli et al, 1981;Panz et al, 2000) which ranged 7-44%, including what was reported in Ethiopia in the 1980s and in 2011 (Gill et al, 2011;Peters et al, 1986). We think that part of the reason why the antibody positivity in our T1DM patients was relatively lower is the fact that most of our T1DM patients were not newly diagnosed as indicated by the mean duration of diabetes.…”
Section: Discussionsupporting
confidence: 51%
“…The UKPDS study, which is one of the largest studies done in patients with type 2 DM, reported a prevalence of 9.4% [9]. Studies conducted amongst Africans have reported the prevalence of GADA in CT2DM as 2.5% amongst South Africans, while in Tanzania the prevalence was 5.3% [10,11]. In a study done in West Africa on the genetics of diabetes, with Ghana and Nigeria as centres, 10% of the patients with CT2DM were found to be positive for GADA [12].…”
Section: Discussionmentioning
confidence: 99%
“…In one European study, two-thirds of a type 1 diabetes cohort were still positive for either islet cell antibodies or GADA at 10 years after diagnosis [26]. Also, type 1 diabetic patients elsewhere in Africa, including urban Ethiopia, have been shown to be positive for GADA or islet cell antibodies [27,28]. Accepting these limitations, our revised groupings give a much more expectable proportion of type 1 diabetes patients at 17%, with type 2 diabetes comprising 47% and the 'uncertain' group 36%.…”
Section: Discussionmentioning
confidence: 99%